CENTRAL ASIA: THE RELIGIOUS SITUATION AND THE THREAT OF RELIGIOUS EXTREMISM - Laumulin, Murat (CENTRAL ASIA AND THE CAUCASUS, 2012)
In Central Asia, religion is gradually coming to the fore in everyday life as a fairly integrated phenomenon with a wide range of functions: consolidation of ethnic self-awareness, shaping spiritual and moral culture together with the awareness of being part of a religious and the world community; fulfilling social functions through religious prescriptions; formulating the ideals of social justice, as well as man’s duty to the state and the state’s to man, etc.Some of the functions, however, are internally contradictory: consolidation of the religious community does not always bring society together. In other words, in some cases religion might exacerbate the relations between the state and the religious part of society.Religious consolidation not infrequently revives old problems and breeds disagreements inside society; conscientious believers often make too rigid demands of the state (which turns them into the opposition), while any encroachments on the religious principle of fairness may stir up protest feelings.In different countries, religious communities have different reasons for and ways of opposing the state; however, there is one common denominator: the gap between the religious interpretation of justice and the duties of the faithful, on the one hand, and state expediency, on the other.Not all religious communities disagree with the state: the Abrahamic religions (Judaism, Christianity, and Islam) insist on obedience to the authorities (since all authority is given by God, Allah). These religious teachings contain certain reservations which permit disobedience, and religious radicals never miss the chance to exploit them.America, which tends to exploit religious radicalism to maintain instability in Central Asia, is another factor of the mounting religiously-motivated extremism and terrorism.This is the context in which religions are functioning in Central Asia.